G12R mutation in Cx26 downregulates the expression levels of TLR2 and its downstream inflammatory factors in keratinocytes - Zhaoying LIU; Yankun LU; Han MA (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To investigate the effect of G12R mutation in Cx26 on the expression of TLR2 and its downstream inflammatory factors in human keratinocytes. Methods Human keratinocytes (HaCaT) without (WT-Cx26) or with G12R-mutation (G12R-Cx26) were co-cultured with Trichophyton rubrum. Expression levels of TLR2 mRNA and its downstream effector molecules were detected by real-time PCR. The expression levels of TLR2 protein were detected by western blot. Cytokine levels in the culture medium were measured by ELISA. Immunofluorescence was used to determine distribution of Cx26 and TLR2 in G12R-Cx26 HaCaT cells. Results Expression levels of TLR2 mRNA were comparable between WT-Cx26 and G12R-Cx26 cells (t=1.92, P=0.190). However, G12R mutation in Cx26 decreased expression levels of TLR2 protein in cell membrane and cytoplasm (both P<0.01 vs. WT-Cx26) in addition to reductions in expression levels of downstream of TLR2 pathway, including TNF (t=6.91, P<0.05), IL-6 (t=13.03, P<0.01) and antimicrobial peptide LL-37 (t=25.31, P<0.001). Coculture of G12R-Cx26 cells with ikarugamycin increased co-localization of Cx26 and TLR2 on the cell membrane. Conclusion Cx26-G12R mutation down-regulates the expression of TLR2 and downstream inflammatory cytokines, including TNF, IL-6 and antimicrobial peptide LL-37, in keratinocytes.